Gestión de inventarios en el centro de repuestos, maquinaria pesada y camiones American Parts, cantón Riobamba, periodo 2021 - Flores Llerena, Angelo Fabricio (2024)
ABSTRACT: The main objective of this research study was to determine how inventory management affects the profitability of the American Parts, heavy machinery, truck center, and spare parts. Inventory management has become a key point for business life, improper management of this negatively affects the company in some cases, leading to the loss of ground in the market, and even low profitability rates. A mixed qualitative-quantitative approach was applied, with a non-experimental design, exploratory, descriptive, documented and field, to obtain the data we worked with the total population of employees of the spare parts center, to whom a survey was applied, which was made up of questions that sought to find out topics such as the diagnosis of the current state of management inventory and analyze its profitability. After the surveys were carried out, a database was designed in Microsoft Excel for analysis, obtaining the following results: 100% of the population affirmed that proper inventory control should be carried out, in which the existing and entering merchandise is coded. To avoid an increase in logistics costs and financially harming the profitability of the American Parts Truck and Heavy Machinery Spare Parts Center. Through the financial statements of the last five years, it was determined that there is a large increase in terms of the annual gross sales profit that has increased each year, observing that in year one it was 240,478.88 and in the last year it was 334,281.68 and showing a final net profit for the last year of 193,136.24 and there is a net flow of cash of 301,128.92, values that can be improved with the proposal of the application of adequate inventory management and stock control. It was evident that there is a lack of coordination between the Logistics, Accounting and Commercial Areas, affecting the good management and economic management of the center, due to not having adequate inventory control, for this reason it is proposed to take a general inventory in the company.